Reviving of adat bersiram tradition and adaptive reuse of Masjid Lama Kampung Tanjung Beringin, Seri Menanti, Negeri Sembilan Darul Khusus - Syahin, Muhammad Amar; Mohd. Din, Shamzani Affendy; Md. Sharif, Harlina (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2019)
Masjid Lama Kampung Tanjung Beringin was built in 1892 by Raja Melewar and the villagers. The mosque is left abandoned for many years without proper care, hence this building has present of defects and missing parts. Restoration an old building with different function has been applied a long time ago with the intention of reviving the building. There are many approaches to revive an old building, such as, adaptive reuse. The aim of this study is to revive the tradition that takes place at Masjid Lama Kampung Tanjung Beringin, Seri Menanti, Negeri Sembilan Darul Khusus through adaptive reuse. The objective of this project is to identify factors causing the functional deterioration of Masjid Lama Kampung Tanjung Beringin, to identify the significance of the mosque in order to revive its function, and to revive the function of the mosque through suitable approach. This study will discover the right process of adaptive reuse and a documentation on the fabric of the site as well as its previous functions as one of its significant value. Perhaps, this study will be beneficial to the people. Specifically, this study analyses eight methods have been used in analysing the site on its motifs, defects, functions, and the design of the mosque in order to fulfil the objective of the study. This study finds the intricate carvings in the mosque that might have related to the reign of Raja Melewar and also related to the adat bersiram tradition that takes place in the mosque. Lastly, this study suggest that adaptive reuse is the best conservation works in hopes it will bring back from the edge of death of this mosque.